2018
DOI: 10.3892/etm.2018.6086
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 overexpression is associated with poor prognosis and oxaliplatin resistance in hepatocellular carcinoma

Abstract: Abstract. Sphingosine kinase 1 (SphK1) is a tumor-associated protein overexpressed in numerous types of cancer and is involved in the regulation of resistance to multiple chemotherapeutic agents. However, the role of SphK1 in the resistance of hepatocellular carcinoma (HCC) to oxaliplatin remains unclear. In the present study, the transcriptional levels of SphK1 were analyzed in 21 patients with HCC and the SphK1 expression levels were identified to be significantly upregulated in HCC tissue compared with that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…High levels of SPHK1 were shown to enhance tumor formation in breast cancer MCF-7 cells 43 . Overexpression of SPHK1 enzyme has also been reported in hepatocellular carcinoma and adrenocortical carcinoma tissues 44,45 . The S1P/SPHK1 axis has also been reported earlier to promote the pancreatic cancer growth by regulating the expression of pancreatic stellate cells 46 .…”
Section: Discussionmentioning
confidence: 94%
“…High levels of SPHK1 were shown to enhance tumor formation in breast cancer MCF-7 cells 43 . Overexpression of SPHK1 enzyme has also been reported in hepatocellular carcinoma and adrenocortical carcinoma tissues 44,45 . The S1P/SPHK1 axis has also been reported earlier to promote the pancreatic cancer growth by regulating the expression of pancreatic stellate cells 46 .…”
Section: Discussionmentioning
confidence: 94%
“…In 2006, Bonhoure et al ( 25 ) reported that SphK1 contributes to MDR-associated chemoresistance in acute myeloid leukemia. The role of SphK1 in chemoresistance has also been investigated in several different types of cancer, including breast ( 26 ), colon ( 27 ) and gastroesophageal cancer ( 28 ), as well as hepatocellular carcinoma ( 12 ). A study conducted by Wang and Wu ( 12 ) reported that SphK1 expression was associated with poor prognosis and oxaliplatin resistance in hepatocellular carcinoma ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, SphK1 and SphK2 have been identified as the two isoforms of SphKs. Considerable attention has been devoted to the involvement of SphK1 in multiple cancers including HCC (10). Recently, the other isoform of SphK, SphK2, also received increasing attention and may be an important regulator of cancer development and progression (11).…”
Section: Introductionmentioning
confidence: 99%